Hepatic Shock Differential Diagnosis and Risk Factors: A Review Article - Soleimanpour, Hassan (Hepat Mon, 2015)
CONTEXT: Liver as an important organ has a vital role in physiological processes in the body. Different causes can disrupt normal function of liver. Factors such as hypo-perfusion, hypoxemia, infections and some others can cause hepatic injury and hepatic shock. EVIDENCE ACQUISITION: Published research resources from 2002 to May 2015 in some databases (PubMed, Scopus, Index Copernicus, DOAJ, EBSCO-CINAHL, Science direct, Cochrane library and Google scholar and Iranian search database like SID and Iranmedex) were investigated for the present study. RESULTS: Different causes can lead to hepatic shock. Most of these causes can be prevented by early resuscitation and treatment of underlying factors. CONCLUSIONS: Hepatic shock is detected in ill patients, especially those with hemodynamic disorders. It can be prevented by early treatment of underlying disease. There is no definite treatment for hepatic shock and should be managed conservatively. Hepatic shock in patients can increase the mortality rate.